The Effect of Professional Skepticism, Investigative Auditor's Experience and Whistleblowing System on Auditor's Ability in Detecting Fraud - Monica Pamela Citranagari (Publikasi Indonesia, 2022)
There is a difference between fraud causing system errors and financial statement errors. References to various national and international cases show that fraud can happen anywhere. This study aims to determine the effect of professional skepticism, auditor experience, and whistleblowing system on the auditor's ability to detect fraud. The population in this study were all private internal and external auditors (Public Accounting Firms). Data collection techniques in this study using a questionnaire. This type of research is a hypothesis testing research. The number of samples collected is 56 respondents. The sampling technique used is convenience sampling. The results of this study indicate that: 1) Professional Skepticism has a positive effect on the auditor's ability to detect fraud. 2) The experience of the investigative auditor has a positive effect on the auditor's ability to detect fraud. 3) The whistleblowing system has a positive effect on the auditor's ability to detect fraud.